Peri-Urban Food Futures: Opportunities and Challenges to Reconfiguring Sustainable Local Agri-food Value Chains on the Sunshine Coast, Australia - Brian R. Stockwell; Elaine Bradley; Deborah Davis; Jonathan Smith (Journal of Agriculture, Food Systems, and Community Development, 2016)
A new rural development paradigm has emerged over the last decade. It is multifaceted by nature, connecting practices of landscape management, agritourism, organic and sustainable farming, and value-chain analysis and management. Increased food production in peri-urban areas in the developed world is typical of this new paradigm. Peri-urban areas are the transitional zones between rural and urban landscapes that experience constant population change and disturbance of traditional social, environmental, and economic characteristics. Sustainable community development initiatives are complicated in these fragmented and often contested landscapes. A case study on Australia's Sunshine Coast analyzes the challenges and opportunities of reconfiguring agri-food production systems to achieve the type of multifunctional landscape preferred by the community and primary producers alike. Scenario analysis, interviews, and surveys of traditional midscale farmers with more recent micro- to small primary producers and food artisans provide insight into the challenges faced at a grassroots level. The role of government in facilitating supportive policy and planning and connecting and building the capacity of key actors involved in local and regional food value chains is reviewed. The paper argues that the government is essential to the successful planning and management of peri-urban areas because of the fragmented and/or contested quality of this unique agri-food landscape. Without further investment in place-based collaborative research, planning, capacity building, and economic development, the local food movement in these peri-urban areas is likely to continue to occupy only a narrow "alternative" cultural and economic space.